1997
DOI: 10.1007/s004180050094
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serotonin-immunoreactive nerve cells and fibers in the rat gastrointestinal tract

Abstract: The distribution of serotonin-immunoreactive (5HT-IR) nerve cells and fibers was thoroughly investigated immunohistochemically in the rat stomach, duodenum, jejunum, ileum, and colon. The immunoreactivity of the 5HT neurons was compared between non-treated controls and animals treated with colchicine, colchicine plus 5-hydroxytryptophan (5HTP), colchicine plus pargyline, and reserpine. The intensity of immunoreactivity in nerve fibers as well as nerve cell bodies was enhanced mostly in colchicine plus pargylin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…For the detection of insulin-or proinsulin-positive cells, we fixed 20-m-thick frozen sections or 5-m-thick paraffin sections and processed them for immunohistochemical staining by using the avidin-biotin peroxidase complex (ABC) method and diaminobenzidine (DAB)-nickel reactions as described (13,15). Briefly, for insulin or proinsulin staining, frozen sections were incubated for 2 days with antibody against insulin (guinea pig polyclonal, Linco Research, St. Charles, MO) or proinsulin (guinea pig polyclonal, Progen, Heidelberg) diluted 1:5,000 in 0.1% PBS containing 0.3% Triton X-100 (PBST) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…For the detection of insulin-or proinsulin-positive cells, we fixed 20-m-thick frozen sections or 5-m-thick paraffin sections and processed them for immunohistochemical staining by using the avidin-biotin peroxidase complex (ABC) method and diaminobenzidine (DAB)-nickel reactions as described (13,15). Briefly, for insulin or proinsulin staining, frozen sections were incubated for 2 days with antibody against insulin (guinea pig polyclonal, Linco Research, St. Charles, MO) or proinsulin (guinea pig polyclonal, Progen, Heidelberg) diluted 1:5,000 in 0.1% PBS containing 0.3% Triton X-100 (PBST) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, 5-HT is known to be present in pulmonary tissues where the source may be pulmonary neuroendocrine cells (50,51) or platelets (52), and thus could facilitate MC accumulation in inflammatory conditions of the lung. Similarly, 5-HT is known to be synthesized by enterochromaffin cells and nerve ganglia in the gastrointestinal system (53)(54)(55), and might influence accumulation of MC at these sites. In summary, we, for the first time, have shown that 5-HT has the ability to influence the biology of the MC.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical investigations confirmed that the majority of serotonin exists in enterochromaffin cells [11, 12]. Serotoninergic neurons in the submucosal layer may contribute to the synthesis of peripheral serotonin as well [13]. Using homogenized tissue extracts from certain regions of the mouse duodenal mucosa, the major enzyme activity of the tryptophan hydroxylase was found to reside between the upper villus region and the bottom of the crypts [9].…”
Section: Introductionmentioning
confidence: 94%
“…Using homogenized tissue extracts from certain regions of the mouse duodenal mucosa, the major enzyme activity of the tryptophan hydroxylase was found to reside between the upper villus region and the bottom of the crypts [9]. This finding had led to the hypothesis that the expression of tryptophan hydroxylase is restricted either to enterochromaffin cells scattered in the mucosal epithelium or to serotoninergic neurons of the nerve plexuses [9, 13, 14]. However, the exact cellular distribution of tryptophan hydroxylase in the gastrointestinal tract has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%